Mainstreaming climate change adaptation into the European Union's development assistance. Issue 81 (March 2018) - De Roeck, Frederik; Orbie, Jan; Delputte, Sarah
Highlights: We find a high level of climate change adaptation mainstreaming in EU aid. A harmonisation of adaptation is upheld throughout the policy cycle. The political salience of adaptation is high and continues to grow. Procedures play little or no role in current mainstreaming efforts. Prioritisation is undermined by organizational and cognitive barriers. Abstract: This paper aims to provide a comprehensive analysis of mainstreaming efforts regarding climate change adaptation (CCA) in EU development cooperation. By constructing and operationalising an analytical framework capable of tracing the level of mainstreaming throughout different phases of the policy cycle, we provide an answer to the question 'what works and what doesn't' in the integration of climate change in development cooperation. We combine a document analysis with semi-structured expert interviews, encompassing both HQ level in Brussels as well as EU aid activities in nine different developing countries. Our findings indicate that the Commission envisions a harmonisation approach towards CCA mainstreaming, targeting aid activities related to sustainable agriculture, food security and rural development. Although the toolbox for mainstreaming allows for a prioritisation of CCA, the procedural approach is currently ineffective due to limited staff and mainstreaming fatigue. In contrast, the growing political salience of CCA mainstreaming can be considered the main driver of mainstreaming efforts in the Commission.